Controlling w systemie szkolenia GOPR - Bielecki, Krzysztof (Controlling in the Mountain Rescue Training System, 2005)
In addition to rescue activities and participation in rescue operation, training within the Volunteer Mountain Rescue Organization is the main field of its activity. It improves the level of the rescue system and thus the level of safety during rescue operations. Strategic and operational controlling introduced to the training system allows the creation of a system solution which may improve its operations and fully realize the postulates necessary for the implementation of a training system. The controlling system will also allow the make optimum use of the resources necessary for training activities, including the financial resources.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 61-66